Bioenergetics: current state, perspectives, foreign experience - Golub, R. (Land Management, Cadastre and Land Monitoring, 2018)
Abstract. Ukraine has good preconditions and sufficient potential for dynamic development of the bioenergy sector. The main driving forces of this process are the constant rise in prices for traditional energy sources and the availability of large biomass potential available for energy use.The most favorable direction for solving the problem is the search for and use of renewable energy sources, among which a new segment of the economy, which is possible on all continents, which includes the production of energy sources of biological origin or biofuels: biodiesel, bioethanol, biogas, is becoming a widespread development. Biofuels throughout the developed world slowly, but confidently squeeze traditional energy.In the context of the aggravation of Ukraine's energy supply, there is a need to revise the structure of available energy sources in favor of renewable energy technologies. The search for and use of biofuels is the most conducive to solving the problem.For Ukraine, bioenergy is one of the strategic directions for the development of the renewable energy sector, given the high dependence of the country on imported energy resources, first of all, on natural gas, and the great potential of biomass available for energy production. Unfortunately, the pace of bioenergy development in Ukraine still lags far behind European ones.Keywords. Bioenergy, biofuels, renewable sources, biomass, energy, consumption.